2022
DOI: 10.1080/0886022x.2022.2079527
|View full text |Cite
|
Sign up to set email alerts
|

TNF-α-mediated podocyte injury via the apoptotic death receptor pathway in a mouse model of IgA nephropathy

Abstract: Background IgA nephropathy (IgAN) is the most common primary glomerular disease worldwide and it is characterized by mesangial IgA deposits. Proteinuria is a common clinical feature of IgAN, which has a critical connection to podocyte injury and has been used as a clinical prognostic factor for IgAN. Evidence has shown that TNF-α released from mesangial cells may lead to podocyte apoptosis. Methods Forty male BALB/c mouse were randomly divided into the control group and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…TNF-α from mesangial cells increases TNF-α synthesis and expression level of TNF receptor 2 (TNFR2) on podocytes, which enhances IL-6 synthesis to induce podocyte apoptosis ( 87 ) and activates the inflammatory response of podocytes ( 57 ) via TNFR1 and TNFR2, respectively. TNF-α-induced podocyte apoptosis was also detected to be associated with increased expression of caspase-3 in renal tissue of mouse model ( 88 ), suggesting TNF-α might induce podocyte apoptosis through TNFR1-/caspase-8/caspase-3 death pathway. Another cell culture experiment demonstrated that TNF-α might induce podocyte apoptosis and foot process effacement through the NF-κB signaling pathway ( 7 ).…”
Section: Podocytementioning
confidence: 92%
“…TNF-α from mesangial cells increases TNF-α synthesis and expression level of TNF receptor 2 (TNFR2) on podocytes, which enhances IL-6 synthesis to induce podocyte apoptosis ( 87 ) and activates the inflammatory response of podocytes ( 57 ) via TNFR1 and TNFR2, respectively. TNF-α-induced podocyte apoptosis was also detected to be associated with increased expression of caspase-3 in renal tissue of mouse model ( 88 ), suggesting TNF-α might induce podocyte apoptosis through TNFR1-/caspase-8/caspase-3 death pathway. Another cell culture experiment demonstrated that TNF-α might induce podocyte apoptosis and foot process effacement through the NF-κB signaling pathway ( 7 ).…”
Section: Podocytementioning
confidence: 92%